2006
DOI: 10.1007/s00018-006-6126-3
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of low-abundant integral plasma membrane proteins based on gels

Abstract: To characterize low-copy integral membrane proteins and offer some methods for human liver proteome projects, we fractionated highly purified rat liver plasma membrane (PM). PM was purified through two sucrose density gradient centrifugations, and treated with 0.1 M Na(2)CO(3), chloroform/methanol and Triton X-100. Proteins were separated by electrophoresis and submitted to mass spectrometry analysis. Four hundred and fifty-seven non-redundant membrane proteins were identified, of which 23% (105) were integral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 38 publications
5
40
1
1
Order By: Relevance
“…However, MALDI-MS/MS is known to identify the most prevalent protein present in a gel spot sample (Jun et al, 2012), and the top-ranked hit resulting from LC-MS/MS analysis has also been shown typically to correspond to the most abundant protein among multiple proteins present in a spot (Yang et al, 2007). The spot intensities of different protein constituents were determined using the protein abundance index and the exponentially modified protein abundance index (emPAI; Supplemental Table S3), which have been routinely applied in proteomics workflows (Perkins et al, 1999;Ishihama et al, 2005;Zhang et al, 2006;Yang et al, 2007;Cilia et al, 2011;Taylor et al, 2011). In this study, if more than one protein was identified in a spot, the relative abundance of each protein was determined by calculating the emPAI from the MS/MS data, and the assumption was made that the most abundant protein would account for the observed regulation (Ishihama et al, 2005).…”
Section: Proteomic Changes In Low-oxalate Transgenic Fruitmentioning
confidence: 99%
“…However, MALDI-MS/MS is known to identify the most prevalent protein present in a gel spot sample (Jun et al, 2012), and the top-ranked hit resulting from LC-MS/MS analysis has also been shown typically to correspond to the most abundant protein among multiple proteins present in a spot (Yang et al, 2007). The spot intensities of different protein constituents were determined using the protein abundance index and the exponentially modified protein abundance index (emPAI; Supplemental Table S3), which have been routinely applied in proteomics workflows (Perkins et al, 1999;Ishihama et al, 2005;Zhang et al, 2006;Yang et al, 2007;Cilia et al, 2011;Taylor et al, 2011). In this study, if more than one protein was identified in a spot, the relative abundance of each protein was determined by calculating the emPAI from the MS/MS data, and the assumption was made that the most abundant protein would account for the observed regulation (Ishihama et al, 2005).…”
Section: Proteomic Changes In Low-oxalate Transgenic Fruitmentioning
confidence: 99%
“…The differential proteins were then analyzed by Ultimate 3000 instruments (Dionex, Germering, Germany) tandem nanoESI-MS-MS (mass spectrometry, Bruker Daltonics, Bremen, Germany) as previously described [19,21]. Briefly, the peptide mixture (5 ml) was directly subjected to a nanoLC-ESI-tandem MS system, including a PepMap TM C18 m-pre-column (300 mm i.d.…”
Section: -De/ms Technologymentioning
confidence: 99%
“…Pooled NPCs from 4-and 8-week time points were analyzed by 2DE using an IPGphor isoelectronic focusing system (GE Healthcare, USA) and Protein II electrophoresis apparatus (Bio-Rad, USA) as described previously [21,25]. A total of 1 mg of protein from each sample was applied to IPG dry strips (pH 3-10 NL, 180 mm×30 mm×0.5 mm).…”
Section: De and Gel Stainingmentioning
confidence: 99%
“…The Protein II electrophoresis apparatus was used to run the 11.5% separation gels. The gels were then stained with Coomassie Blue G-250 as described previously [25].…”
Section: De and Gel Stainingmentioning
confidence: 99%